Seismic fragility assessment of existing masonry buildings in aggregate. (15th November 2021) - Angiolilli, Michele; Lagomarsino, Sergio; Cattari, Serena; Degli Abbati, Stefania
Abstract: The paper describes the derivation of fragility curves useful for the seismic risk analyses of existing unreinforced masonry buildings inserted in aggregate. The L-shaped examined aggregate consists of three adjacent structural units that may mutually interact during seismic events. The seismic assessment is focused on the corner unit. The effects of different connection types between the adjacent units on the structural response were investigated. The seismic vulnerability of the masonry aggregate was assessed through nonlinear dynamic analyses (NDA) performed according to the multi-stripes approach. Both the in-plane and out-of-plane mechanisms were analyzed. The in-plane response of the corner unit is assessed through a 3D equivalent frame model of the entire aggregate, while the evaluation of its out-of-plane response makes use of the rigid-block assumption. Although evaluated in a separate way, the NDAs performed on the latter are based on the time histories derived from the global 3D model. The results are then processed in order to derive fragility curves, firstly, of the single failure mechanisms and, then, of the overall combined behavior. To this aim, various performance conditions are examined. For the reference building, the damage limit state is mainly governed by the in-plane behavior, while the collapse limit state by out-of-plane mechanisms. Moreover, the higher the connection level between adjacent structural units, the higher the interaction between in-plane and out-of-plane mechanisms at the collapse limit state. Highlights: Procedure for derivation of fragility curves by NLDA accounting for both in-plane and out-of-plane mechanisms. The 3D equivalent frame model of the aggregate considers the interaction between buildings by proper joints. Rigid block NLDAs of the OOP response use time histories derived from the 3D model of the aggregate. For the corner building, damage limit state is governed by IP response while collapse by OOP mechanisms. The higher the connection between structural units, the higher the interaction of IP and OOP at collapse.